IMAGERY: A VIRTUAL LABORATORY FOR TRAINING ON DIGITAL IMAGE PROCESSING - Montenegro Joo, Javier (2006)
Digital Image Processing (DIP) books teach algorithms to digitally operate on images and include some figures to show the effects of those mathematical tools. In this report the creation of Imagery, a Virtual Laboratory for computer-assisted education (teaching and learning) of DIP is reported. Imagery can be used in the classroom, in the laboratory or at home. This software was developed to be used as a DIP laboratory, allowing the user to experiment with DIP algorithms, enabling him to see their effects on his own images. In the classroom Imagery helps the teacher in the exposition of the DIP topics he is covering; in the laboratory, Imagery can be used to carry out experiments supporting the topics covered in class; at home, this Virtual Lab can be used by the student to practice and thus reinforce the knowledge acquired in class. This software may also be used by the independent student or by that under a Distant Learning program. The advantage of using software to teach a given image transformation like those performed in DIP, is that with the help of the software the transformations can be appreciated in real time. Besides being intuitively easy to use, Imagery not only operates on images included by its author, but also on those provided by the user. The author has included some supporting theory in Imagery, which is a complement to specialized textbooks or classes, it is not self sufficient, however it is a great help.